Aufnahme von Duro Ladipo in einer Gruppe von Menschen während der Eröffnung des Mbari Mbayo Club in Osogbo (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1962)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Painting; Africa; Exhibitions; Art Exhibition; Mbari Mbayo Club; Osogbo; Nigeria; Cultural Centre; Performing Arts Center